Damage analysis of RC beams without web reinforcement - Köksal, HO; Arslan, G (THOMAS TELFORD SERVICES LTD, 2004)
This paper presents the results of non-linear finite element analyses to predict the shear strength of reinforced concrete beams without web reinforcement. The improvement of a single parameter damage model previously proposed for the general behaviour of the concrete is achieved to provide a better description for the flexural behaviour of reinforced concrete beams, which is strongly affected by tensile cracking. Twenty-four beams well known in the literature are evaluated for the validation of the model. Given an optimum size and a regular mesh configuration, the whole load-deflection behaviour of the beams is analysed and the main results of the numerical analyses are presented. Unlike many numerical investigations, emphasis is placed not only on good prediction of the ultimate strength but also on diagonal cracking and deformational behaviour: The results front the non-linear analyses are employed to derive a simple relation for prediction of the diagonal cracking load of the reinforced concrete beams including the normalised beam depth to take the size effect into consideration. The predictions of the proposed relation are compared with the test data and the values obtained from the expressions recommended by ACI and Zsutty.
Keywords: SHEAR-STRENGTH; CONCRETE BEAMS; FINITE-ELEMENT; PREDICTION; PLASTICITY; MODEL; Construction & Building Technology; Materials Science